Nitrogen-capped π-prismands: syntheses and conformational analyses - Kunze, Andreas; Bethke, Sabine; Gleiter, Rolf; Rominger, Frank (Organic letters, 2000)
The one-pot syntheses of the new diazabicyclophanes 5−7 are described. The benzene rings incorporated in the bridging chains exhibit rotational motion which is examined by means of variable-temperature NMR experiments and semiempirical calculations. X-ray analysis and NMR studies indicate that the metal ion in the endohedral silver(I) complex of 7 fluctuates between the two nitrogen atoms.